Elements of bioenvironmental engineering - Gaudy, Anthony F. (Engineering Press, 1988)
This volume may be used as a reference in courses dealing with biological aspects of pollution control. An abbreviated version of the authors' textbook entitled "Microbiology for Environmental Scientists and Engineers" (McGraw Hill, 1980), the book covers: The Life-Support System; Technological Control of Water Quality; Chemical Composition of Cells and the Nature of Organic Matter; The Microorganism; Nutrition and Growth Conditions as Selective Agents in Natural Populations; Quantitative Description of Growth; Energy Generation and Utilization in Biological Systems; Metabolic Classification of Microorganisms; The Central Pathways of Metabolism; Aerobic Metabolism; and Anaerobic Metabolism. Chapters 1 through 10 conclude with references and suggested readings; a glossary and list of symbols are also provided.